Correction to: Unveiling Emerging Interdisciplinary Research Challenges in the Highly Threatened Sclerophyllous Forests of Central Chile (Revista Chilena de Historia Natural, 2024 97 1 7 10.1186/S40693-024-00130-Y) - Zorondo-Rodriguez, F (BioMed Central Ltd, 2024)
Following publication of the original article [1], the authors would like to update Affiliation 7 details. Please see below for the correct details: 7Center for Ecology and Sustainable Management of Oceanic Islands (ESMOI), Department of Marine Biology, Faculty of Marine Sciences, Universidad Católica del Norte, Coquimbo, Chile. 7ESMOI-Center for Ecology and Sustainable Island Management, Coquimbo, Chile. This correction does not affect the overall result or conclusion of the article. The original article [1] has been corrected. © The Author(s) 2024.